Interseksionalitas dalam Pendidikan Inklusif di Indonesia - Dharmika Pranidhi (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the implementation of inclusive education with a gender equality perspective in Indonesia, focusing on the gap between policy and practice, particularly for vulnerable groups such as girls with disabilities. Using a literature review (2020–2025), theoretical analysis (intersectionality, gender theory, inclusive education), and a case study of the Women’s School in Bali, the research finds that implementation remains partial and faces structural and cultural barriers, including gender stereotypes and limited teacher capacity. The case study highlights the potential of community-based approaches that integrate GEDSI (Gender Equality, Disability, and Social Inclusion) and local wisdom to strengthen inclusive practices. The study emphasizes the need for systemic transformation through intersectional approaches, deconstruction of gender norms, and multi-stakeholder collaboration. Recommendations include strengthening intersectional policies, transformative teacher training, inclusive curricula, equitable resource allocation, and participatory research and monitoring.